Pollen-food allergy syndrome in children - You Hoon Jeon (The Korean Pediatric Society, 2020)
Pollen-food allergy syndrome (PFAS) is an immunoglobulin E-mediated immediate allergic reaction caused by cross-reactivity between pollen and the antigens of foods-such as fruits, vegetables, or nuts-in patients with pollen allergy. A 42.7% prevalence of PFAS in Korean pediatric patients with pollinosis was recently reported. PFAS is often called oral allergy syndrome because of mild symptoms such as itching, urticaria, and edema mainly in the lips, mouth, and pharynx that appear after food ingestion. However, reports of systemic reactions such as anaphylaxis have been increasing recently. This diversity in the degree of symptoms is related to the types of trigger foods and the characteristics of allergens, such as heat stability. When pediatric patients with pollen allergy are treated, attention should be paid to PFAS and an active effort should be made to diagnose it.